CCR7 Is Important for Mesangial Cell Physiology and Repair. (January 2018) - Wurm, Simone; Steege, Andreas; Rom-Jurek, Eva-Maria; van Roeyen, Claudia R.; Kurtz, Armin; Banas, Bernhard; Banas, Miriam C.
The homeostatic chemokine receptor CCR7 serves as key molecule in lymphocyte homing into secondary lymphoid tissues. Previous experiments from our group identified CCR7 also to be expressed by human mesangial cells. Exposing cultured human mesangial cells to the receptor ligand CCL21 revealed a positive effect on these cells regarding proliferation, migration, and survival. In the present study, we localized CCR7 and CCL21 during murine nephrogenesis. Analyzing wild-type and CCR7 deficient (CCR7 –/– ) mice, we observed a retarded glomerulogenesis during renal development and a significantly decreased mesangial cellularity in adult CCR7 –/– mice, as a consequence of less mesangial cell proliferation between embryonic day E17.5 and week 5 postpartum. Cell proliferation assays and cell-wounding experiments confirmed reduced proliferative and migratory properties of mesangial cells cultured from CCR7 –/– kidneys. To further emphasize the role of CCR7 as important factor for mesangial biology, we examined the chemokine receptor expression in rats after induction of a mesangioproliferative glomerulonephritis. Here, we demonstrated for the first time that extra- and intraglomerular mesangial cells that were CCR7-negative in control rats exhibited a strong CCR7 expression during the phase of mesangial repopulation and proliferation.